Collaboration between HPMC and NaCMC in order to Reach the Polymer Critical Point in Theophylline Hydrophilic Matrices. (1st August 2012) - Contreras, L.; Melgoza, L. M.; Aguilar-de-Leyva, A.; Caraballo, I.
Abstract : Percolation theory has been applied in order to study the existence of critical points as well as the possibility to find a "combined percolation threshold" for ternary hydrophilic matrices prepared with HPMC, NaCMC, and theophylline. For this purpose, different batches of ternary as well as binary hydrophilic matrices have been prepared. Critical points have been found for binary hydrophilic matrices between 21.5 and 31.3% (v/v) of HPMC and between 39 and 54% (v/v) of NaCMC, respectively. In a previous work carried out with the same polymers but a much more soluble drug (KCl), it was demonstrated the existence of a partial collaboration between the polymers in order to establish the gel layer. In this work, it has been observed for the first time the need of a minimum concentration of one of the matrix-forming polymer (between 10 and 20% v/v, approximately) for establishing an effective collaboration.